2020
DOI: 10.1002/csc2.20201
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms facilitate distinctness‐uniformity‐stability testing of soybean cultivars for plant variety protection

Abstract: Plant variety protection (PVP), or plant breeders’ rights, provides intellectual property protection (IPP) for cultivars. Technical requirements are distinctness, uniformity, and stable (DUS) reproduction. However, field trials are increasingly resource demanding and potentially inconclusive for soybean (Glycine max [L.] Merr.). Our objective was to establish methodologies using molecular markers to facilitate DUS testing while maintaining current IPP levels. We determined that DNA from 10–15 bulked plants rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 79 publications
(98 reference statements)
1
19
0
1
Order By: Relevance
“…This study showed that the BARCSoySNP6K assay was able to discriminate accessions among landrace, elites and wild soybean as we predicated. Similarly, Liu et al (2017) found that associations among 577 Chinese and US soybean cultivars utilizing the 6K reflected the geographical origins and pedigrees of the cultivars, showing no indication of ascertainment bias within or among these sets of soybean germplasm, similar results were also reported by Achard et al (2020).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…This study showed that the BARCSoySNP6K assay was able to discriminate accessions among landrace, elites and wild soybean as we predicated. Similarly, Liu et al (2017) found that associations among 577 Chinese and US soybean cultivars utilizing the 6K reflected the geographical origins and pedigrees of the cultivars, showing no indication of ascertainment bias within or among these sets of soybean germplasm, similar results were also reported by Achard et al (2020).…”
Section: Discussionsupporting
confidence: 57%
“…For example, Qi et al (2014) generated 33.10 Gb of data by GBS in soybean, the average sequencing depth was greater than 429 for the two parents, and 3.929 for each of 149 lines, the resulting linkage maps included 5308 markers on 20 linkage groups, of these markers, in total, 3231 had unique genotypic profiles among the lines, the remaining 2077 markers co-segregated with one of the 3231 SNPs in the population. Li et al (2015) analyzed three wheat RIL populations using reads from GBS and constructed genetic maps containing 28 644 SNPs, of these, approximately 13% (3757) had unique segregation patterns in the population, the remaining 87% (24 887 SNP selection bias or ascertainment bias can result from the selection of highly discriminating SNPs utilizing one set of germplasm, but which might then be found to be less usefully discriminating among another unrelated set of germplasm (Achard et al, 2020). For the initial discovery of the SNPs to be included in the SoySNP50K assay, a set of eight genotypes, including six diverse cultivated and two wild soybean genotypes, were sequenced (Song et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 20,046 SNPs showed polymorphism between parental cultivars. The low polymorphism found between the parental lines might be due to the reduced genetic diversity existed among soybean cultivars that resulted as a consequence of domestication and development of commercial varieties (Li et al 2013;Achard et al 2020). The genetic map construction and QTL analysis were performed using the polymorphic markers in QTL IciMapping Ver.…”
Section: Linkage Mapping and Qtl Analysismentioning
confidence: 99%